Triple-layered encapsulation through direct droplet impact - Yin, Shuai (2022)
Multilayer capsules not only provide better protection for the core, but also enable multifunctionalities. However, their fabrication is challenging. Rapid encapsulation by the impact of the droplet is a simplified approach to form the compound droplet with a single shell layer. Therefore, it is worth exploring the potential for multilayer capsule formation with the approach.